2004
DOI: 10.1111/j.1601-5223.1996.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical Characteristics of the Common Shrews (Sorex Araneus L.) from Interracial Hybrid Zones

Abstract: Common shrews are subdivided into numerous chromosome races which make contact and form hybrid zones. To date, no strong differences in morphology have been found between hybrid and pure race individuals from the vicinity of such hybrid zones. To investigate this further, we carried out studies in Poland on three hybrid zones between races belonging to the West and East European Karyotypic Groups using material collected from 1989 to 1994. Shrews were measured (head and body, tail and hindfoot length) and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…For 4 of 22 traits examined we found significant differences between the hybrids and the representatives of the Tomsk race. It is interesting that Chêtnicki et al (1996) detected that the hybrids between the Stobnica (WEKG) and £êgucki M³yn (EEKG) races were more similar in their morphology to the latter pure race. It is not clear if it is only a coincidence that morphological characteristics of the EEKG races (£êgucki M³yn and Novosibirsk) dominate in hybrids with races of West European (Stobnica) and Siberian (Tomsk) origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 4 of 22 traits examined we found significant differences between the hybrids and the representatives of the Tomsk race. It is interesting that Chêtnicki et al (1996) detected that the hybrids between the Stobnica (WEKG) and £êgucki M³yn (EEKG) races were more similar in their morphology to the latter pure race. It is not clear if it is only a coincidence that morphological characteristics of the EEKG races (£êgucki M³yn and Novosibirsk) dominate in hybrids with races of West European (Stobnica) and Siberian (Tomsk) origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, a case of significant morphological differences has been described in Poland, between shrews of two parapatric chromosome races representing distinct karyotypic groups (Chêtnicki et al 1996). Animals of the Stobnica (WEKG) and £êgucki M³yn (EEKG) races were distinguished from each other as well as from interracial hybrids by a study of external morphometrics.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the Stobnica and £êgucki M³yn races in Poland (Chêtnicki et al 1996), the only known instance of clear morphological differentiation of parapatric chromosome races in S. araneus involves the Valais race. In the western Alps, Hausser et al (1991) could distinguish between Sorex coronatus, the race Valais and a third group consisting of the races Vaud, Bretolet, and Cordon by a discriminant analysis based on a set of 26 orthogonal measurements (method described in Hausser 1984).…”
Section: Morphologymentioning
confidence: 99%
“…Although a number of researchers have found morphological differences between the chromosomal races of Sorex araneus (Chętnicki et al, 1996;Polyakov et al, 2002;Okulova et al, 2007), in most studies, morphometric variability was unassociated with racial boundaries (Sulkava et al, 1985;Searle & Thorpe, 1987;Wójcik et al, 2000;Banaszek et al, 2003;Mishta, 2007). Morphological difference was found in cases when the races differed in size.…”
Section: Discussionmentioning
confidence: 99%
“…So, the remarkable karyotypic diversity of the species is not congruent to its morphological differentiation. Indeed, at least two cases of clear morphological divergence were found between races of different karyotypic groups (Chętnicki et al, 1996;Polyakov et al, 2002). Moska and Paśko (2006) found that though individuals of races from the same karyotypic group (Lęgunski Młyn and Popielno) do not clearly differ, canonical analysis and multidimensional scaling allow discrimination between hybrids and non-hybrids.…”
Section: Introductionmentioning
confidence: 99%